Understanding exploration, appraisal and production stages - Ganat, T.A.-A.O. (Springer, 2020)
Exploration is a costly and risky operation as the expenditure associated are generally valued at millions of dollars and every two out of three wells, on average, contain no shows of hydrocarbons. Consequently, the exploration companies need to drill more wells in one area to find an oil or gas discovery, and this might take more years. Â© The Author(s), under exclusive license to Springer Nature Switzerland AG 2020.